Site Selection for Lobster Culture in Floating Cage using Multi-criteria Analysis - Muhammad Junaidi; Nanda Diniarti; Nunik Cokrowati; Alis Mukhlis; Baiq Hilda Astriana; Flaxen D. L. Conway (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Spiny lobster is as a very promising culture commodity to be developed due to their high demand in the domestic and global markets. The selection of the suitable location was one of determining factors for the success of lobster cultivation. Various criteria are required for the location of lobster cultivation, both technically and biologically. This research aimed to analyze the suitability sites for lobster culture in floating cages using Multi-criteria Analysis and Geographic Information System (GIS). The research was conducted in May 2018 in North Lombok Regency Water, West Nusa Tenggara. A survey method was applied and used primary and secondary data. Data collected were grouped into 3 categories i.e. oceanographic parameter (water depth, current, wave, and transparency), water quality (temperature, salinity, pH, dissolved oxygen, nitrate, and phosphate), and socio-economic and institutional parameters (legality, easy access, labor availability, and market). Primary data were obtained by measuring oceanography and water quality parameters at 23 observation points on eight transects perpendicular to the coast. Socio-economic and institutional data were obtained from the relevant agencies. Data analysis was done by combining Multi-criteria Analysis and GIS. The result of this research shows that the water condition still supports mariculture activity. The total area covered by this research was 9,087 ha, of which 1,226 ha were found very suitable for lobster culture using floating cage.